Trauma-focused cognitive behavioral therapy a clinical trial to increase self-efficacy in abused the primary school children - Vahid Farina; Safora Salemi; Faezeh Tatari; Nasrin Abdoli; Touraj Ahmadi Jouybari; Mostafa Alikhani; Behrad Basanj; Ali Zakiei (Wolters Kluwer Medknow Publications, 2018)
Background: Child abuse and violence toward children has become a complex phenomenon in nowadays societies leaving hurt children with numerous complications such as lowered self-efficacy. Hence, this study was conducted to assess the effect of trauma-focused cognitive behavioral therapy (TF-CBT) in physically abused children self-efficacy. Materials and Methods: This study was a randomized clinical trial. From this statistical population of all abused children aged 9-12 in Kermanshah in 2016-2017, 40 were divided into intervention and control groups randomly. Tools used in this study were Maurice self-efficacy questionnaire and child abuse questionnaire. Data analysis was done using Chi-square test, paired t-test, and independent t-test. Results: It was revealed that the mean difference between two groups was not meaningful before intervention. After TF-CBT in intervention group, self-efficacy mean scores of social (17.95 vs. 24.20) and emotional (15.05 vs. 19.05) domains showed meaningful differences, whereas academic self-efficacy mean score did not change significantly (14.10 vs. 14.65) (P < 0.086). In control group, social (16.20 vs. 15.55), emotional (13.90 vs. 14.35), and academic (13.40 vs. 13.90) mean self-efficacy scores were not of significant difference (P > 0.001). Conclusions: TF-CBT can be used as an appropriate therapy intervention to improve social and emotional self-efficacy in abused children.